2016
DOI: 10.1111/1744-7941.12098
|View full text |Cite
|
Sign up to set email alerts
|

The effects ofLMXon gender discrimination and subjective career success

Abstract: The objectives of this study are to identify the effects of leader–member exchange (LMX) on employees' perception of gender discrimination and subjective career success and to examine the relationship between gender discrimination and subjective career success. Data was collected from hotel employees in Seoul, South Korea. To accomplish the objectives, structural equation modeling was conducted.The first result was that LMX had a significant positive impact on subjective career success. Second, LMX impacted di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 84 publications
(158 reference statements)
2
12
0
3
Order By: Relevance
“…Men are accorded 'masculine' attributes such as assertiveness, agency, achievement focus and bravery, and women the 'feminine' attributes of communality, supportiveness and empathy (Diekman and Eagly, 2000;Schein, 1973Schein, , 1975. These persistent gender stereotypes influence the assignment and determination of social roles (Kim et al, 2016;Park et al, 2017). Thus, men are considered to more naturally fit leadership positions because these roles are believed to require masculine characteristics (Powell et al, 2002;Schein, 1973Schein, , 1975.…”
Section: Gender Differences In Innovative Work Behaviour Empowermentmentioning
confidence: 99%
“…Men are accorded 'masculine' attributes such as assertiveness, agency, achievement focus and bravery, and women the 'feminine' attributes of communality, supportiveness and empathy (Diekman and Eagly, 2000;Schein, 1973Schein, , 1975. These persistent gender stereotypes influence the assignment and determination of social roles (Kim et al, 2016;Park et al, 2017). Thus, men are considered to more naturally fit leadership positions because these roles are believed to require masculine characteristics (Powell et al, 2002;Schein, 1973Schein, , 1975.…”
Section: Gender Differences In Innovative Work Behaviour Empowermentmentioning
confidence: 99%
“…Hal ini dapat terjadi karena adanya perbedaaan peran pekerjaan dan tingkat jabatan di organisasi atau perusahaan. inovatif ini (W. Kim et al, 2016;Park et al, 2017;Powell et al, 2002).…”
Section: Salsabiah Firdausiah Arum Etikarienaunclassified
“…Akan tetapi, hasil penelitian ini tidak tidak sejalan dengan penelitian yang dilakukan dalam konteks organisasi seperti penelitian Østergaard (2011) dan Janssen (2000) yang menemukan adanya perbedaan perilaku kerja inovatif antara perempuan dan laki-laki. Hal ini bisa saja terjadi karena dalam organisasi lakilaki lebih sering memegang jabatan yang lebih tinggi, sehingga memiliki kekuasaan yang berbeda dalam menerapkan perilaku kerja inovatif (Kim et al, 2016;Park et al, 2017;Powell et al, 2002). Sedangkan, di universitas tidak ada perbedaan tingkat jabatan seperti itu.…”
Section: Pembahasanunclassified
“…34 Only with the transfer of mutual aid between neighbors can a reciprocal relationship develop. 34 Previous research revealed that social relationships provide essential social resources for individuals to cope with stressful events 35 and improve themselves. 36 Given the scarce economic resources available to low-income employees, social resources are relatively important for them.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…14 Moreover, both received and given neighboring behavior have long-lasting effects on social relationships between neighbors, providing low-income employees with ongoing social resources for maintaining good mental health 37 and achieving career satisfaction in the workplace. 35 By examining the mediation effect of both family interference with work and work interference with family, this research reveals the underlying mechanism through which career satisfaction and mental health are impacted by supportive neighboring behavior. Work-family conflict arises from incompatible stressors from work and family.…”
Section: Theoretical Implicationsmentioning
confidence: 99%